Membranes for Low Temperature Fuel Cells : New Concepts, Single-Cell Studies and Applications. - Sharma, Surbhi (Walter de Gruyter GmbH, 2019)
Membranes for Low Temperature Fuel Cells provides a comprehensive review of novel and state-of-the-art polymer electrolyte membrane fuel cells (PEMFC) membranes. The author highlights requirements and considerations for a membrane as an integral part of PEMFC and its interactions with other components. It is an indispensible resource for anyone interested in new PEMFC membrane materials and concerned with the development, optimisation and testing of such membranes. Various composite membranes (polymer and non-polymer) are discussed along with analyses of the latest fi ller materials like graphene, ionic liquids, polymeric ionic liquids, nanostructured metal oxides and membrane concepts unfolding in the field of PEMFC. This book provides the latest academic and technical developments in PEMFC membranes with thorough insights into various preparation, characterisation, and testing methods utilised. Factors affecting proton conduction, water adsorption, and transportation behaviour of membranes are also deliberated upon. Provides the latest academic and technical developments in PEMFC membranes. Reviews recent literature on ex situ studies and in situ single-cell and stack tests investigating the durability (chemical, thermomechanical) and degradation of membranes. Surbhi Sharma, MSc, PhD Working on graphene oxide and fuel cells since 2007, she has published about 50 research articles/book chapters and holds a patent. She has also been awarded various research grants.
Keywords: Proton exchange membrane fuel cells -- Materials.; Membranes (Technology); elektronické knihy; electronic books